The type 1 insulin-like growth factor receptor pathway - Chitnis, Meenali M; Yuen, John S P; Protheroe, Andrew S; Pollak, Michael; Macaulay, Valentine M (Clinical cancer research, 2008)
Research conducted over the past two decades has shown the importance of the type 1 insulin-like growth factor receptor (IGF1R) in tumorigenesis, metastasis, and resistance to existing forms of cancer therapy. The IGF1R itself has only recently been accepted as a credible treatment target, however, perhaps reflecting the potential problems for drug design posed by normal tissue IGF1R expression, and close homology with the insulin receptor. Currently approximately 12 anti-IGF1R therapeutics are undergoing clinical evaluation, including blocking antibodies and tyrosine kinase inhibitors. This review will summarize the principal signaling pathways activated by IGF1R and the preclinical data that validated this receptor as a treatment target. We will review clinical progress in the testing of IGF1R inhibitory drug candidates, the relative benefits and potential toxicities of coinhibition of the insulin receptor, and the rationale for combining IGF1R blockade with other cancer treatments. An understanding of IGF1R signaling is important because it will guide the incorporation of appropriate molecular markers into clinical trial design. This will be key to the identification of patients most likely to benefit, and so will influence the ability of IGF1R inhibition to make the transition from experimental intervention to clinical therapy.